PENGARUH PENGGUNAAN PEMBELAJARAN THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS X SMA NEGERI 15 PADANG - Zulfikarni, Rori Harapan, Ellya Ratna, (Universitas Negeri Padang, 2017)
This article was written to describe the influence of cooperative learning TPS concerning short story writing skill of class X students of SMAN 15 Padang. The data of this research were the result of the short story writing final test. The data were collected by giving short story writing test through cooperative learning TPS and without cooperative learning TPS. The hipotesis tested by using test-t formula. The result indicated that (1) the arithmetic average of the students’ short story writing skills pretest 72,91; (2) the arithmetic average of the students’ short story writing skills posttest were 80,69; and (3) according to test-t’s result, can be concluded that there was a significant influence of the used of cooperative learning TPS to the short story writing skill of class X students of SMAN 15 Padang. Kata kunci: pengaruh, TPS, menulis cerpen